Generating anatomical variation through mutations in networks – implications for evolution. Issue 2 (17th June 2014) - Bard, Jonathan
Abstract Genetic mutation leads to anatomical variation only indirectly because many proteins involved in generating anatomical structures in embryos operate cooperatively within molecular networks. These include gene‐regulatory or control networks (CNs) for timing, signaling and patterning together with the process networks (PNs) for proliferation, apoptosis, differentiation and morphogenesis that they control. This paper argues that anatomical variation is achieved through a two‐stage process: mutation alters the outputs of CNs and perhaps the proliferation network, and such changed outputs alter the ways that PNs construct tissues. This systems‐biology approach has several implications: first, because networks contain many cooperating proteins, they amplify the effects of genetic variation so enabling mutation to generate a wider range of phenotypes than a single changed protein acting alone could. Second, this amplification helps explain how novel phenotypes can be produced relatively rapidly. Third, because even organisms with novel anatomical phenotypes derive from variants in standard networks, there is no genetic barrier to their producing viable offspring. This approach also clarifies a terminological difficulty: classical evolutionary genetics views genes in terms of phenotype heritability rather than as DNA sequences. This paper suggests that the molecular phenotype of the classical concept of a gene is often a protein network, with a mutation leading to an alteration in that network's dynamics.